Legal Risk Management in Sharia Bank Contracts - Lubis, Rahmat Husein; Batubara, Sarmiana (Ijtimā iyya Journal of Muslim Society Research, 2025)
A crucial aspect of Islamic banking activities is the existence of contracts, which are agreements that bind the parties in financial transactions. However, in practice, there are legal risks arising from unclear contracts, differences in legal interpretation, and non-compliance with regulations. This risk can have an impact on the operational stability of Islamic banks and reduce public trust. The purpose of this study is to examine the forms of legal risks in Islamic bank contracts and their risk management mitigation strategies. The methodology used is a qualitative approach based on a literature analysis related to Islamic banking regulations, fatwas, and practices in Indonesia. The findings of this study confirm that legal risks can arise due to unclear contracts, violations of sharia principles, and non-compliance with regulations such as DSN-MUI fatwas and OJK regulations. These risks are found in murabahah, mudharabah, musyarakah, ijarah, istisna', and others, including defaults, data misuse, and juridical weaknesses. Recommended mitigation strategies include drafting clear contracts, sharia compliance audits, monitoring contract implementation, and education to customers. With effective legal risk management, Islamic banks can improve operational stability and public trust, while ensuring the sustainability of the Islamic banking industry in Indonesia